(untitled) (Journal of Nepalese Business Studies, 2018)
Securities market turnover is one of the major behavioral phenomena of stock market. It always depends on the demand and supply of the securities, so the market turnover assumes a number of trading share units, values of share turnover and percentage share value of stocks. This paper is concerned to analyze the different areas of stock units’ turnover and value coverage of stock market .descriptive research design is applied for analyzing the stock market condition. The coverage of share units and share of value weight is analyzed of Nepal stock exchange market economy. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page: 96-100